Impact of Gender-Based Violence on Psychological Wellbeing among People Living with HIV/AIDS: A Case of Kibera Community Health Centre - Oino, Emma (Daystar University, School of Applied Human Sciences, 2024)
Gender-based violence is a pervasive issue that disproportionately affects people living with HIV/AIDS, particularly in resource-constrained areas like the Kibera community in Nairobi, Kenya. This study sought to investigate the prevalence of GBV among PLWHA in Kibera community, determine their psychological well-being, evaluate the impact of GBV on their psychological well-being and examine the mediating effect of sociodemographic factors. The study was guided by the Ecological Systems Theory and the Minority Stress Theory, which provided a framework for understanding the complex interplay of individual, interpersonal, community, and societal factors that influence GBV and psychological well-being among PLWHA. This study used a descriptive crosssectional research design, targeting a population of adult PLWHA (aged 18 years or more) who were registered at the Kibera Community Health Centre. The target population of the study was 5,000 PLWHA registered at the Kibera Community Health Centre. The sample size of the study was 371, determined using the Yamane formula, and included adult PLWHA (aged 18 years and above) who were residents of the Kibera community and were registered at the Kibera Community Health Centre. The study used stratified random sampling. The pretesting involved administering the questionnaires to a sample of 30-50 PLWHA who were not part of the main study sample. The pretest sample was selected using random sampling from the target population of PLWHA registered at the SHOFCO community health center. Data analysis involved descriptive and inferential statistics using SPSS version 23. The study found that gender-based violence was prevalent among people living with HIV/AIDS in the Kibera community, with over 50% of participants reporting experiences of physical, sexual, emotional, and economic violence. The psychological wellbeing of participants was moderately compromised, with varying levels of positive experiences across different domains. A negative correlation was found between genderbased violence and psychological wellbeing (r=-0.637, p=0.000), with gender-based violence explaining 40.6% of the variance in psychological wellbeing scores. Sociodemographic factors, including age, gender, education level, and income, were found to play a significant role in mediating the relationship between gender-based violence and psychological wellbeing. The study concludes that gender-based violence is a critical issue affecting the psychological wellbeing of people living with HIV/AIDS in the Kibera community, with sociodemographic factors playing a significant mediating role in this relationship. The study recommends that comprehensive screening for gender-based violence should be integrated into routine HIV care and support services, accompanied by clear referral pathways to appropriate support services. Mental health support should be integrated into HIV care services to address the compromised psychological wellbeing of people living with HIV/AIDS. Interventions addressing both gender-based violence and mental health should be developed and implemented within HIV care and support programs, adopting a holistic and trauma-informed approach. These interventions should be tailored to account for various sociodemographic factors, including age-specific programs, gender-sensitive approaches, education and health literacy programs, and economic empowerment initiatives. Further research is recommended to explore additional variables that may influence the relationship between gender-based violence and psychological wellbeing among people living with HIV/AIDS in similar resourceconstrained settings.
MASTER OF ARTS in Clinical Psychology
Keywords: Gender-based violence; HIV/AIDS; Psychological well-being